Opportunities of improvement in the management of pancreatic and periampullary tumors. (May 2013) - Nordby, Tom; Ikdahl, Tone; Lothe, Inger Marie Bowitz; Ånonsen, Kim; Hauge, Truls; Edwin, Bjørn; Line, Pål-Dag; Labori, Knut Jørgen; Buanes, Trond
Abstract Objective. The first objective of the present study was to identify opportunities of improvement for clinical practice, assessed by local quality indicators, then to analyze possible reasons why we did not reach defined treatment quality measures. The second objective was to characterize patients, considered unresectable according to present criteria, for future arrangement of interventional studies with improved patient selection. Material and methods. Prospective observational cohort study from October 2008 to December 2010 of patients referred to the authors' institution with suspected pancreatic or periampullary neoplasm. Results. Of 330 patients, 135 underwent surgery, 195 did not, 129 due to unresectable malignancies. The rest had benign lesions. Perioperative morbidity rate was 32.6%, mortality 0.7%. Radical resection (R0) was obtained in 23 (41.8%) of 55 patients operated for pancreatic adenocarcinoma and 6.3% underwent reconstructive vascular surgery. Diagnostic failure/delay resulted in unresectable carcinoma, primarily misconceived as serous cystic adenoma in two patients. One resected lesion turned out to be focal autoimmune pancreatitis. One case with misdiagnosed cancer was revised to be a pseudoaneurysm. Palliative treatment was offered to 144 patients with malignant tumors, 62 due to locally advanced disease and all pancreatic adenocarcinomas. Conclusions. Quality improvement opportunities were identified for patient selection and surgical technique: Too few patients underwent reconstructive vascular surgery. The most important quality indicators are those securing resectional, radical (R0) surgery. Altogether 143 patients (57.9%) of those with malignant tumors were found unresectable, most of these patients are eligible for inclusion in future interventional studies with curative and/or palliative intention.